2021
DOI: 10.3389/fonc.2021.768168
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiotherapy in Brain Malignancies: Indications and Outcomes in Primary and Metastatic Brain Tumors

Abstract: Despite the continued controversy over defining an optimal delivery mechanism, the critical role of adjuvant radiation in the management of surgically resected primary and metastatic brain tumors remains one of the universally accepted standards in neuro-oncology. Local disease control still ranks as a significant predictor of survival in both high-grade glioma and treated intracranial metastases with radiation treatment being essential in maximizing tumor control. As with the emergence and eventual acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…In this context, different others modalities of adjuvant radiotherapy are currently assessed in a goal to improve local control and/ or reduce brain toxicity such as intraoperative radiotherapy or intra operative brachytherapy; several published studies have reported a high variability in term of one-year-local control, from 50% [ 31 ] to 88% with a low rate of radionecrosis (7%) [ 32 ]. Larger prospective studies are needed to confirm these favorable results including combination with systemic treatment [ 33 ]. The role of a novel collagen Tile cesium brachytherapy is currently in tested.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, different others modalities of adjuvant radiotherapy are currently assessed in a goal to improve local control and/ or reduce brain toxicity such as intraoperative radiotherapy or intra operative brachytherapy; several published studies have reported a high variability in term of one-year-local control, from 50% [ 31 ] to 88% with a low rate of radionecrosis (7%) [ 32 ]. Larger prospective studies are needed to confirm these favorable results including combination with systemic treatment [ 33 ]. The role of a novel collagen Tile cesium brachytherapy is currently in tested.…”
Section: Discussionmentioning
confidence: 99%
“…To delay tumor recurrence, radiotherapy and chemotherapy are used as adjuvant therapies 35 . Radiation therapy is an important supplement to glioma treatment, with conventional radiation doses of 50–60 Gy 36–38 . It may be possible to conduct radiotherapy using an external source, an internal source, or radioactive monoclonal antibodies 39 .…”
Section: Current Status Of Glioma Therapiesmentioning
confidence: 99%
“…35 Radiation therapy is an important supplement to glioma treatment, with conventional radiation doses of 50-60 Gy. [36][37][38] It may be possible to conduct radiotherapy using an external source, an internal source, or radioactive monoclonal antibodies. 39 Temozolomide (TMZ) is a first-line agent for GBM therapy, 40 but some patients with TMZresistance have less than ideal therapeutic effect.…”
Section: Standard Therapy: Surgery Chemotherapy and Radiotherapymentioning
confidence: 99%
“…While SRS and WBRT have been extensively evaluated in the last few decades for management of brain metastases, another mode of radiation therapy that is increasingly gaining attention is intraoperative radiotherapy (IORT) (64). IORT involves a single dose of radiation administered at the same time as the surgical biopsy or resection being performed.…”
Section: Intraoperative Radiotherapymentioning
confidence: 99%